Genetic Engineering of the Kidney to Permanently Silence MHC Transcripts During ex vivo Organ Perfusion - Yuzefovych, Yuliia; Valdivia, Emilio; Rong, Song; Hack, Franziska; Rother, Tamina; Schmitz, Jessica; Bräsen, Jan Hinrich; Wedekind, Dirk; Moers, Cyril; Wenzel, Nadine; Gueler, Faikah; Blasczyk, Rainer; et al. (Frontiers in Immunology, 2020)
Organ gene therapy represents a promising tool to correct diseases or improve graft survival after transplantation. Polymorphic variation of the major histocompatibility complex (MHC) antigens remains a major obstacle to long-term graft survival after transplantation. Previously, we demonstrated that MHC-silenced cells are protected against allogeneic immune responses. We also showed the feasibility to silence MHC in the lung. Here, we aimed at the genetic engineering of the kidney towards permanent silencing of MHC antigens in a rat model. We constructed a sub-normothermic ex vivo perfusion system to deliver lentiviral vectors encoding shRNAs targeting β2-microglobulin and the class II transactivator to the kidney. In addition, the vector contained the sequence for a secreted nanoluciferase. After kidney transplantation (ktx), we detected bioluminescence in the plasma and urine of recipients of an engineered kidney during the six weeks of post-transplant monitoring, indicating a stable transgene expression. Remarkably, transcript levels of β2-microglobulin and the class II transactivator were decreased by 70% in kidneys expressing specific shRNAs. Kidney genetic modification did not cause additional cell death compared to control kidneys after machine perfusion. Nevertheless, cytokine secretion signatures were altered during perfusion with lentiviral vectors as revealed by an increase in the secretion of IL-10, MIP-1α, MIP-2, IP-10 and EGF and a decrease in the levels of IL-12, IL-17, MCP-1 and IFNγ. Biodistribution assays indicate that the localization of the vector was restricted to the graft. This study shows the potential to generate immunologically invisible kidneys showing great promise to support graft survival after transplantation and may contribute to reduce the burden of immunosuppression.